الضبط الإداري في مجال الصحة (دراسة حالة كوفيد 19) - بن قلية, علي (جامعة الوادي -University eloued, 2022)
تستهدف هده الورقة التعرض لدراسة الإجراءات الوقائية لتصدي لفيروس كورونا في الجزائر، فمند ظهور جائحة كورونا بالصين وضعت الحكومة الجزائرية العديد من التدابير والإجراءات الوقائية، وذلك لحماية صحة وسلامة المواطنين وتفادي انتشار فيروسكوفيد-19، وعلى هدا الأساس فالدراسة تسعي إلى تحديد مفهوم كل من فيروس كورونا وأسباب انتشاره في الجزائر، بالإضافة إلى تسليط الضوء على أهم التدابير والإجراءات التي اتخذتها This paper aims to expose the study of preventive measures to tackle the Corona virus in Algeria. Since the emergence of the Corona pandemic in China, the Algerian government has put in place several preventive measures and measures, in order to protect the health and safety of citizens and avoid the spread of the Covid-19 virus, and on this basis the study seeks to define the concept of each virus Corona, the reasons for its spread in Algeria, the concept of quarantine and its procedures, in addition to highlighting the most important measures and measures that Algeria has taken and its effectiveness in facing the Corona virus.
ماستر اداري
Keywords: الإجراءات الوقائية، فيروس كورونا، الحكومة الجزائرية، الحجر الصحي; Preventive Measures, Corona Virus, Algerian Government, Quarantine.